Flipped Classroom Approach for Enhancing Vocabulary Skills among Senior High Schools in the Philippines - Claire Angela R. Luna; Jeric Z. Romero; Karen J. Cusi Karen J. Cusi; Amelia A. Jarapa; Adhi Kusuma (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aimed to examine the effects of the flipped classroom approach on learners' vocabulary enrichment, specifically focusing on students' vocabulary skills under this method. Conducted at Calayan Educational Foundation, Inc., the study involved 105 Grade 11 senior high school students from the academic track, comprising 68 STEM, 23 HUMSS, and 14 ABM students, who completed validated questionnaires. The findings revealed a significant improvement in vocabulary skills after implementing the flipped classroom approach. While traditional teaching methods—such as repetition, drills, and direct instruction—are effective for younger learners in vocabulary acquisition, they may be less suitable for secondary-level students. The study demonstrated that a modified flipped classroom approach is highly effective for Grade 11 academic strand students. This method emphasizes learning by doing rather than memorization, allowing students to gain knowledge and develop vocabulary skills applicable in real-life situations.